2018
DOI: 10.1111/sum.12421
|View full text |Cite
|
Sign up to set email alerts
|

European long‐term field experiments: knowledge gained about alternative management practices

Abstract: Alternative management practices such as no‐tillage compared to conventional tillage are expected to recover or increase soil quality and productivity, even though all of these aspects are rarely studied together. Long‐term field experiments (LTEs) enable analysis of alternative management practices over time. This study investigated a total of 251 European LTEs in which alternative management practices such as crop rotation, catch crops, cover crops/green manure, no‐tillage, non‐inversion tillage and organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 44 publications
6
64
4
Order By: Relevance
“…This complicates the decision making process even further. Consequently, there is no such thing as a one size (or soil) fits all soil strategy, which is in line with the findings of Sandén et al (2018). Decisions must therefore be based on careful considerations accounting for local demands, their soils' potential to deliver functions and even ecosystem services, as well as synergies and trade-offs between soil functions and the weightings of alternative options for achieving these services.…”
Section: Discussionmentioning
confidence: 85%
“…This complicates the decision making process even further. Consequently, there is no such thing as a one size (or soil) fits all soil strategy, which is in line with the findings of Sandén et al (2018). Decisions must therefore be based on careful considerations accounting for local demands, their soils' potential to deliver functions and even ecosystem services, as well as synergies and trade-offs between soil functions and the weightings of alternative options for achieving these services.…”
Section: Discussionmentioning
confidence: 85%
“…The aim of management is to improve soil physical, chemical, and biological quality in order to overcome yield-limiting (e.g., soil moisture) and yield-reducing (e.g., pests) factors. In order to confirm a positive or negative effect of a management practice on primary productivity, longterm experiments can function as living laboratories (Johnston and Poulton, 2018;Sandén et al, 2018). Zavattaro et al (2015) observed slight yield reductions following application of organic amendments, including farmyard manure and incorporation of crop residues, most likely due to N immobilization.…”
Section: Primary Productivity Decision Support Modelmentioning
confidence: 99%
“…Although uncertainties about the achievable magnitude of future soil C sequestration exist, many long-term experiments (LTEs) have shown that the consistent application of certain management practices does increase the OC content of agricultural soils (Paustian et al, 1997;Ogle et al, 2005;Chenu et al, 2018). An increase in SOC stocks is achievable through management practices that increase C inputs to the soil, such as the addition of organic fertilizers (Haynes and Naidu, 1998;Sandén et al, 2018), the incorporation of crop residues in the soil after harvest (Lehtinen et al, 2014) or the cultivation of cover crops (Poeplau and Don, 2015). In contrast, practices that aim to reduce SOC losses, such as no-till, generally lead to a mere redistribution of OC along the soil profile while not significantly increasing total SOC stocks (Luo et al, 2010;Powlson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although increasing the OC content of soils can lead to a net removal of CO 2 from the atmosphere, trade-offs with N 2 O emissions should be taken into account, as these can reduce or completely offset the climate mitigation effect of certain management practices (Gao et al, 2018). For example, while the application of farmyard manure (FYM) can significantly increase topsoil OC stocks (Bai et al, 2018;Sandén et al, 2018Sandén et al, , 2019b, an accompanying increase in N 2 O emissions can offset this benefit (Zhou et al, 2017). Similar observations have been made for crop rotations including cover crops, which can increase topsoil OC stocks significantly (Poeplau and Don, 2015), while N 2 O emissions can increase substantially when their biomass is decomposed (Basche et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation